2015
DOI: 10.1371/journal.pone.0123279
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Alendronate Is Associated with a Decreased Incidence of Type 2 Diabetes Mellitus—A Population-Based Cohort Study in Taiwan

Abstract: PurposeBone remodeling has been linked to glucose metabolism in animal studies, but the results of human trials were inconclusive. Bisphosphonates may play a role in glucose metabolism through their impacts on bone remodeling enzymes. In this study, we aimed to examine the influence of alendronate usage on the incidence of type 2 diabetes mellitus (DM) among osteoporotic patients.MethodsA retrospective cohort study was designed to include osteoporotic patients without DM from a population-based cohort containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
(21 reference statements)
2
22
0
1
Order By: Relevance
“…Additional reports found that osteocalcin functions like a hormone which adjusts fat mass and glucose metabolism in genetically modified mouse display reduced insulin resistance, glucose intolerance, and betacell proliferation [3].Moreover, osteocalcin consumption controlled gene expression in adipocytes and betacells and also impacted the improvement of metabolic disease, obesity, as well as type 2 diabetes mellitus in wild type mice [4], accordance to experimental animal scientific studies; osteocalcin concentrations are proven to be reduced in-individuals with type 1 diabetes mellitus and type 2 diabetes mellitus [5]. On the other hands, it would seem there's adverse association between osteocalcin serum levels as well as glycosylated hemoglobin; together with better control diabetes, amounts of osteocalcin is going to be increase [6].Though, a few scientific studies are carried out that don't verify the association [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…Additional reports found that osteocalcin functions like a hormone which adjusts fat mass and glucose metabolism in genetically modified mouse display reduced insulin resistance, glucose intolerance, and betacell proliferation [3].Moreover, osteocalcin consumption controlled gene expression in adipocytes and betacells and also impacted the improvement of metabolic disease, obesity, as well as type 2 diabetes mellitus in wild type mice [4], accordance to experimental animal scientific studies; osteocalcin concentrations are proven to be reduced in-individuals with type 1 diabetes mellitus and type 2 diabetes mellitus [5]. On the other hands, it would seem there's adverse association between osteocalcin serum levels as well as glycosylated hemoglobin; together with better control diabetes, amounts of osteocalcin is going to be increase [6].Though, a few scientific studies are carried out that don't verify the association [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…65 In rodent models study, 66 antiresorptive therapy with reductions in ucOC and OC could lead to insulin resistance, lower insulin secretion, weight gain and an increased risk of diabetes. On the contrary, some studies 64,67 found that antiresorptive therapy does not have a clinically important effect on fasting glucose, weight or diabetes risk. Result of observational studies of the longitudinal effects of OC and ucOC levels on glucose metabolism have been inconsistent.…”
Section: Effects Of Bisphosphonates On Bone Loss In Diabetes Mellitusmentioning
confidence: 98%
“…63 BPs, potent inhibitors of osteoclastic activity, do suppress bone turnover and decrease systemic uOC levels. 64 Therefore, BP therapies, which reduce ucOC levels, may increase the risk of insulin resistance and diabetes. Alendronate has been shown to reduce ucOC by 56%.…”
Section: Effects Of Bisphosphonates On Bone Loss In Diabetes Mellitusmentioning
confidence: 99%
“…Although, some studies are done which do not confirm this association. [96, 97]. Despite the fact that taking alendronate would cause decrease in the OC and ucOC levels, two recently published cohort studies have shown that alendronate might reduce the risk of developing Type 2 diabetes [96, 97].…”
Section: Main Textmentioning
confidence: 99%
“…[96, 97]. Despite the fact that taking alendronate would cause decrease in the OC and ucOC levels, two recently published cohort studies have shown that alendronate might reduce the risk of developing Type 2 diabetes [96, 97]. One explanation for this paradox could be the not exactly identified role of ucOC in human glucose metabolism [98].…”
Section: Main Textmentioning
confidence: 99%